Enhanced preventive programme at a beryllium oxide ceramics facility reduces beryllium sensitisation among new workers. Issue 2 (16th October 2006) - Cummings, Kristin J; Deubner, David C; Day, Gregory A; Henneberger, Paul K; Kitt, Margaret M; Kent, Michael S; Kreiss, Kathleen; Schuler, Christine R
Abstract : Background: A 1998 survey at a beryllium oxide ceramics manufacturing facility found that 10% of workers hired in the previous 6 years had beryllium sensitisation as determined by the beryllium lymphocyte proliferation test (BeLPT). In response, the facility implemented an enhanced preventive programme to reduce sensitisation, including increased respiratory and dermal protection and particle migration control. Aim: To assess the programme's effectiveness in preventing sensitisation. Methods: In 2000, the facility began testing newly hired workers for beryllium sensitisation with the BeLPT at time of hire and during employment. The sensitisation rate and prevalence for workers hired from 2000 to 2004 were compared with that for workers hired from 1993 to 1998, who were tested in the 1998 survey. Facility environmental conditions for both time periods were evaluated. Results: Newly hired workers in both cohorts worked for a mean of 16 months. Of the 97 workers hired from 2000 to 2004 with at least one employment BeLPT result, four had abnormal results at time of hire and one became sensitised during employment. Of the 69 workers hired from 1993 to 1998 and tested in 1998, six were found to be sensitised. The sensitisation rate for the 2000–4 workers was 0.7–2.7/1000 person-months of employment, and that for the 1993–8 workers was 5.6/1000 person-months, at least 2.1 (95% confidence interval (CI) 0.6 to 8.4) and up to 8.2 (95% CI 1.2 to 188.8) times higher than that for the 2000–4 workers. The sensitisation prevalence for the 2000–4 workers was 1% and that for the 1993–8 workers was 8.7%, 8.4 (95% CI 1.04 to 68.49) times higher than that for the 2000–4 workers. Airborne beryllium levels for production workers for the two time periods were similar. Conclusions: A comprehensive preventive programme reduced beryllium sensitisation in new workers during the first years of employment, despite airborne beryllium levels for production workers that were similar to pre-programme levels.